Esquema de reproductores macho de referencia para un núcleo genético disperso de alpacas (Vicugna pacos) Huacaya en la región Pasco, Perú - Amanca H., Eliet (2018)
The alpaca herds in Pasco region, Peru, have few known genetic links, so the breeding value of sires from different herds cannot be compared since environmental effects can mask the genetic differences among them. The aim of the study was to evaluate a sire referencing scheme for a dispersed genetic nucleus of Huacaya alpacas in Pasco. Data was collected to evaluate the organizational capacity of the breeders and characterize the population structure of six herds belonging to the nucleus in 2016. The size of the nucleus was calculated based on the need for annual replacement of sires. The genealogy was simulated for three scenarios of sire reference schemes (SRS) with 3, 6 and 9 males mating 10, 20 and 30% of dams in the nucleus per generation respectively. The contemporary groups (CG) were determined by herd-year for three generations. Finally, the degree of the genetic link was calculated using the method of total number of direct genetic links (TDGL) among CG. Results showed that the evaluated herds have a central and open genetic structure, with a low flow of animals between the nucleus and the based group. The minimum size of the dispersed genetic nucleus was 747 dams and 41 males. The three SRS scenarios in the dispersed genetic nucleus showed a high degree of genetic link in three generations, ranged from 98.20 to 100% of TDGL.